2014
DOI: 10.1186/1471-2474-15-227
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hypothalamic-pituitary-adrenal axis activity in chronic multi-site musculoskeletal pain: partly masked by depressive and anxiety disorders

Abstract: BackgroundStudies on hypothalamic-pituitary-adrenal axis (HPA-axis) function amongst patients with chronic pain show equivocal results and well-controlled cohort studies are rare in this field. The goal of our study was to examine whether HPA-axis dysfunction is associated with the presence and the severity of chronic multi-site musculoskeletal pain.MethodsData are from the Netherlands Study of Depression and Anxiety including 1125 subjects with and without lifetime depressive and anxiety disorders. The Chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 51 publications
(84 reference statements)
2
57
1
4
Order By: Relevance
“…The distinct findings might also be explained by measurement differences, for example, in the assessment of pain, depression or cortisol 37. Several cross-sectional studies showed biological alterations in chronic pain3 8 also in the Netherlands Study of Depression and Anxiety sample 9 12. Our current finding of no associations with chronic pain onset might therefore suggest that these biological changes are consequences rather than risk factors for developing this condition.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…The distinct findings might also be explained by measurement differences, for example, in the assessment of pain, depression or cortisol 37. Several cross-sectional studies showed biological alterations in chronic pain3 8 also in the Netherlands Study of Depression and Anxiety sample 9 12. Our current finding of no associations with chronic pain onset might therefore suggest that these biological changes are consequences rather than risk factors for developing this condition.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, interaction effects were tested with life events and with psychopathology that are known to influence biological stress systems functioning. Thus, if dysregulated biological stress systems would play an important role in the onset of chronic pain, our study should have been able to show this, especially since our cross-sectional findings did indicate biological alterations in chronic pain 9 12…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Otonom sinir sisteminde parasempatik sistem aktivitesinin azalması, sempatik sistemin aşırı aktivitesi ile strese verilen yanıtın değişmesi, sensitizasyonu indükleyebilmektedir. [34] PATOFİZYOLOJİ TEMELLİ TEDAVİLER Ağrıda nosiseptif ve inflamatuvar ağrı mekanizmaları hakim ise basit analjezikler (parasetamol), nonsteroidal ağrı kesiciler ya da daha şiddetli ağrılarda güçlü analjezikler olarak opioidler kullanılmaktadır. Kronik ağrı, tedavisi güç bir hastalıktır.…”
Section: Ri̇sk Faktörleri̇unclassified